2014
DOI: 10.1371/journal.pone.0090117
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Mediated Inhibition of TNFR1 Attenuates Disease in a Mouse Model of Multiple Sclerosis

Abstract: Tumour necrosis factor (TNF) is a proinflammatory cytokine that is known to regulate inflammation in a number of autoimmune diseases, including multiple sclerosis (MS). Although targeting of TNF in models of MS has been successful, the pathological role of TNF in MS remains unclear due to clinical trials where the non-selective inhibition of TNF resulted in exacerbated disease. Subsequent experiments have indicated that this may have resulted from the divergent effects of the two TNF receptors, TNFR1 and TNFR2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(86 citation statements)
references
References 48 publications
6
76
0
Order By: Relevance
“…Inhibition of soluble TNF or TNFR1 increases the specificity of the treatment by targeting the proinflammatory axis of TNF signaling while leaving the regulatory TNFR2 pathway intact. Consequently, several studies suggest that specific inhibition of soluble TNF or TNFR1 in autoimmune diseases might be sufficient to achieve benefits similar to those of TNF antagonists, but without causing side effects (12,41,42). Although we did not address this issue, we do show that genetic ablation of TNFR1 is sufficient to partially protect mice from the full-blown skin inflammation upon IMQ treatment.…”
Section: Discussionmentioning
confidence: 55%
“…Inhibition of soluble TNF or TNFR1 increases the specificity of the treatment by targeting the proinflammatory axis of TNF signaling while leaving the regulatory TNFR2 pathway intact. Consequently, several studies suggest that specific inhibition of soluble TNF or TNFR1 in autoimmune diseases might be sufficient to achieve benefits similar to those of TNF antagonists, but without causing side effects (12,41,42). Although we did not address this issue, we do show that genetic ablation of TNFR1 is sufficient to partially protect mice from the full-blown skin inflammation upon IMQ treatment.…”
Section: Discussionmentioning
confidence: 55%
“…However, of relevance, the BBB undergoes rapid changes in permeability in response to CNS insults, e.g., after spinal cord injury or during MS, potentially enabling therapeutics to reach the CNS parenchyma without specific transport mechanisms. Indeed, the reported therapeutic activity of ATROSAB in EAE models (40) supports this reasoning. Whether alterations of the BBB permeability in different neurodegenerative diseases are sufficient to reach therapeutic effective concentrations in the CNS is presently unclear.…”
Section: Resultsmentioning
confidence: 75%
“…However, preclinical studies in the experimental autoimmune encephalomyelitis (EAE) model (36)(37)(38) or a mouse model of spinal cord injury (39) revealed that selective neutralization of sTNF/TNFR1 signaling is neuroprotective. Of note, in the EAE model, systemic application of TNFR1-blocking antibodies proved to be therapeutically effective (40). Accordingly, TNFR1 antagonists such as ATROSAB should be superior to conventional anti-TNF drugs in the treatment of neurodegenerative diseases, as they spare TNFR2 and even enhance TNFR2 signaling but still block detrimental signals transmitted via TNFR1.…”
Section: Resultsmentioning
confidence: 99%
“…A particular role of TNFR1 in MS is suggested by genome-wide association studies, which found a polymorphism in the TNFR1 gene that is linked to increased susceptibility for MS but not to other autoimmune diseases [68]. Moreover, TNFR1 is essential for the disease induction of experimental autoimmune encephalomyelitis (EAE), the animal model of MS, whereas TNFR2 deficiency exacerbates the disease [69][70][71][72]. Of interest for the development of novel anti-TNF therapeutics is also the finding that mice expressing non-cleavable memTNF are protected against EAE, suggesting that the interaction of sTNF with TNFR1 is responsible for the pathology [73].…”
Section: Pathophysiology Of Tnf Deregulationmentioning
confidence: 99%
“…Since TNFR1 is essential for the development of EAE, we recently applied a commercial hamster IgG specific for mouse TNFR1 [116] to evaluate the potential of antibody-mediated anti-TNFR1 treatment in EAE [72]. Interestingly, a single dose of the antibody (5 mg/kg) was sufficient to ameliorate the disease when given at the time of disease induction.…”
Section: Tnfr1-specific Antibodiesmentioning
confidence: 99%